Effects of nano-sized sodium hexametaphosphate on the viability, metabolism, matrix composition, and structure of dual-species biofilms of Streptococcus mutans and Candida albicans - Sampaio, Caio [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Hosida, Thayse Yumi [UNESP]; Morais, Leonardo Antônio de [UNESP]; Fernandes, Ana Vitória Pereira [UNESP]; Souza Neto, Francisco Nunes [UNESP]; Camargo, Emerson Rodrigues de; Monteiro, Douglas Roberto; Pessan, Juliano Pelim [UNESP] (Taylor & Francis, 2022)
This study evaluated the effects of micrometric or nano-sized sodium hexametaphosphate (HMPnano), combined or not with fluoride (NaF, 1100 ppm), on dual-species biofilms of Streptococcus mutans and Candida albicans. Biofilms were treated with solutions containing the polyphosphates at 0.5% or 1.0%, with/without fluoride (F), in addition to positive and negative controls. Biofilms were analysed by colony-forming units (CFU) counting, metabolic activity, production of biomass, composition of extracellular matrix, and structure. 1% HMPnano + F led to the lowest S. mutans CFU, while C. albicans CFU counts were not affected by any solution. 1% HMPnano led to the lowest metabolic activity, except for 1% HMPnano + F. All solutions promoted reductions in biofilm biomass compared to controls. Also, 1% HMPnano + F promoted the lowest concentrations of carbohydrates in the biofilm matrix, besides substantially affecting biofilms’ structure. In conclusion, HMPnano and F promoted higher antibiofilm effects compared with its micrometric counterpart for most of the parameters assessed.
Keywords: biofilms; Candida albicans; fluorides; nanotechnology; Phosphates; Streptococcus mutans